Relationship between clinical features and distant metastases in rectal cancer predicted based on a nomogram: a retrospective cohort study - Qiong Jia; Guoli Li; Min Zhang; Mingyue Guo (Scientific Reports)
Abstract Rectal cancer is a prevalent global malignancy. Recurrence and metastasis significantly impact patient survival over the long term. This study aims to identify independent risk factors associated with distant metastases in rectal cancer (RC) patients and develop a prognostic columnar-line diagram. This retrospective analysis encompasses data from 1,118 RC patients treated at the Department of Anorectal Surgery, Chifeng Municipal Hospital, between December 2015 and October 2023. These patients were diagnosed with stage I-IV RC. Univariate and multivariate Cox proportional hazard regression models identified risk factors for distant metastases development. The median follow-up duration was 61.3 months (range 2.24–96.33 months). The identified factors linked to distant metastases in RC included hemoglobin levels, body mass index (BMI), leukocyte neutrophil percentage, tumour diameter, pathology type, differentiation degree, number of detected lymph nodes, and T and N stages. These factors are significant risk indicators for distant metastases in RC patients. Incorporating these identified risk factors into a columnar-line diagram effectively predicts the likelihood of distant metastasis in RC patients. This approach aids in devising precise treatment strategies during the initial patient consultation.